Data4Ag: Profiling presents opportunities for smallholders - Reeve, Sophie (Technical Centre for Agricultural and Rural Cooperation, 2018)
Aggregating information about farm location and production in farmer profiles helps companies to tailor their support for smallholders, but how can this data be securely managed and transferred to rural farmers for their benefit?